To approximate solution to a problem of filtration theory for small values of TIME - Jamuratov Kengash; Nafasov Ganisher Abdurashidovich (Zien Journals, 2023)
The problem of unsteady filtration, which subsequently modeled as a boundary value problem with an unknown moving boundary section. We prove the existence and uniqueness of the solution of the problem in the small.
Keywords: filtration; evaporation; interface; approximation